An Irish Palladian in England, the case of Sir Edward Lovett Pearce - Hayes, Melanie (Four Courts Press, 2021)
This article charts Sir Edward Lovett Pearce’s complex connections from country estates in Norfolk, courtly circles in Surrey and fashionable enclaves in Mayfair to the newly-built streets of Dublin’s North City. Drawing together the fruits of existing scholarship and new lines of enquiry, it explores the myriad connections which Pearce established on both sides of the Irish Sea, and their consequence in terms of the spread of architectural ideas between the two kingdoms – Ireland and Great Britain – in the early Georgian period. In so doing it fleshes out our understanding of the English context to Pearce’s architectural practice.
Living Legacies: Ireland's National Historic Properties in the care of the OPW
PUBLISHED
Dublin
Keywords: Making Ireland; Architecture; Architecture History; British History; Early Modern Britain and Ireland; Early modern ireland, colonial communities; English and European architecture, 18th and 19th centuries; European Architecture; History of Architecture; Irish History; Irish and British History 1500-1800; Irish architecture, 18th and 19th centuries